2018
DOI: 10.1055/s-0038-1675231
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial and Infratentorial Approaches to Pineal Surgery: A Database Analysis

Abstract: Objectives Neoplasms involving the pineal gland are rare. When they do occur, tumor resection is anatomically challenging and is traditionally addressed by either a supratentorial or an infratentorial approach. To date, no large, multicenter studies have been performed that systematically analyze outcomes comparing these two approaches. This study aimed to evaluate outcomes for patients undergoing pineal neoplasm resection, comparing supratentorial and infratentorial approaches. Design Retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Most surgical series of resection of pineal tumors of various histologies with sufficient detail on postoperative follow-up report on the experience of single institutions, often even single surgeons [ 64 ]. Postoperative morbidity of resective procedures in recent monoinstitutional series ranges between 19% and 22% [ 33 , 35 , 41 , 49 , 62 , 63 , 65 , 66 , 67 ], with up to 45.6% adverse events in the period of 30 days after surgery [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most surgical series of resection of pineal tumors of various histologies with sufficient detail on postoperative follow-up report on the experience of single institutions, often even single surgeons [ 64 ]. Postoperative morbidity of resective procedures in recent monoinstitutional series ranges between 19% and 22% [ 33 , 35 , 41 , 49 , 62 , 63 , 65 , 66 , 67 ], with up to 45.6% adverse events in the period of 30 days after surgery [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…complications for patients undergoing surgical procedures. 13,14 Previous studies have shown a low disagreement rate when this database was audited. 15 NSQIP has been used in the surgical field to track the preoperative data and postoperative outcomes of individual patients.…”
Section: Methodsmentioning
confidence: 95%